‘Doctors for export’ - Jones, Greta. (Leiden ; Boston)
xiv, 248 sayfa
Keywords: “This is the first full-length study of doctor migration from Ireland covering roughly a century of the export of Irish medical graduates to other parts of the world. From 1860 around forty percent of Ireland's medical graduates left to pursue careers elsewhere. The book examines the factors which drove emigration, the shifting destinations of the emigrants and the effect of migration both upon them and the Ireland they left behind. This was the migration of a part of the Irish middle class, small in terms of Irish emigration as a whole, but important in the global history of medical migration. At the end of the twentieth century doctor migration as a whole has increased and become a significant part of the medical experience. The book is a contribution to the growing literature on the global history of doctor movements across the world.“ --